Paper 91: Anteroinferior Glenoid Rim Fractures in Shoulder Instability Patients Over 50: A Matched Cohort Analysis of Risk Factors, Treatment Strategies, and Outcomes. Issue 7 (30th July 2022) - Smartt, Anne; Song, Bryant; Wilbur, Ryan; Reinholz, Anna; Till, Sara; Okoroha, Kelechi; Krych, Aaron; Camp, Christopher
Objectives: Background: Although they are common, there remains a paucity of data regarding traumatic anterior shoulder dislocations (ASI) associated with anteroinferior glenoid rim fractures (AGRF) in older patients. Purpose: To describe the incidence of AGRF in this population following ASI, identify risk factors for AGRF, compare treatment strategies, and compare clinical outcomes of patients with and without an associated AGRF. Methods: An established geographic medical record system was used to identify patients >50 years of age with ASI between 1994 and 2016. Patients with radiographic evidence of AGRF were identified and matched 1:1 to patients without AGRF. Comparative analysis was conducted to determine differences between groups. Results: Overall, 186 patients were identified with a mean follow-up of 10.4 years (range, 2.0 – 25.4). Of these, 42 (22.6%) had AGRF and were matched to 42 control patients without AGRF. Average age was 58.9 and 58.2 years for the AGRF and control groups, respectively. Rates of surgical intervention (29% vs. 43%), recurrent instability (14% vs. 17%), progression of osteoarthritis (34% vs. 39%), and conversion to arthroplasty (2% vs. 5%) were similar between AGRF and control cohorts. Control patients were more likely to report recurrent pain (p=.046). For patients with AGRF, increased bone fragment size (OR 1.1) and increased BMI (OR 1.2) correlated with an increased risk for surgery. The cut-off value for surgery in patients with AGRF was a fragment size ≥33% of the glenoid width. Conclusions: In patients ≥ 50 years at presentation of ASI, 22.6% presented with an associated AGRF. Increased fragment size and greater patient BMI were significant factors associated with undergoing surgical intervention; however, most patients did not require surgery. Patients without AGRF were more likely to report recurrent pain, possibly due to a higher prevalence of rotator cuff derangement. Overall, the presence of an AGRF did not portend a worse prognosis as treatment strategies and long-term outcomes in terms of recurrent instability, progression of osteoarthritis, and conversion to arthroplasty were similar between patients with and without AGRF at the time of ASI diagnosis.